2022
DOI: 10.14202/vetworld.2022.1719-1726
|View full text |Cite
|
Sign up to set email alerts
|

Predicting body weight of Kalahari Red goats from linear body measurements using data mining algorithms

Abstract: Background and Aim: The Kalahari Red goat breed is the finest meat-producing species in South Africa, and its coat color ranges from light to dark red-brown. A practical approach to estimating their body weight (BW) using linear body measurements is still scarce. Therefore, this study aimed to determine the best data mining technique among classification and regression trees (CART), Chi-square automatic interaction detection (CHAID), and exhaustive CHAID (Ex-CHAID) for predicting the BW of Kalahari Red goats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, Eyduran et al [ 10 ] indicated that the regression techniques cannot overcome the multi-collinearity problems from the variables. Hence, some studies used different data mining algorithms such as the classification and regression trees (CART) in South African Boer goats [ 6 ], chi-squared automatic interaction detector (CHAID) in South African indigenous non-descript goats [ 12 ], exhaustive CHAID in Kalahari Red goats [ 13 ] and multivariate adaptive regression splines (MARS) in Pakistani goats [ 9 ] for more and better developmental breeding strategies. Eyduran et al [ 14 ] indicated that these data mining algorithms were also useful for the estimation of fleece weight from the wool characteristics of sheep.…”
Section: Introductionmentioning
confidence: 99%
“…However, Eyduran et al [ 10 ] indicated that the regression techniques cannot overcome the multi-collinearity problems from the variables. Hence, some studies used different data mining algorithms such as the classification and regression trees (CART) in South African Boer goats [ 6 ], chi-squared automatic interaction detector (CHAID) in South African indigenous non-descript goats [ 12 ], exhaustive CHAID in Kalahari Red goats [ 13 ] and multivariate adaptive regression splines (MARS) in Pakistani goats [ 9 ] for more and better developmental breeding strategies. Eyduran et al [ 14 ] indicated that these data mining algorithms were also useful for the estimation of fleece weight from the wool characteristics of sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric measurements are routinely used in everyday practice to provide information for selection purposes. Different studies reported a strong correlation between some morphometric measurements and production traits [ 20 , 21 , 22 , 23 ]. Moreover, linear body measurements are important data sources for portraying breed standards.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of body weight from morphometric traits is a cheap, easy and indirect method that can be practiced by livestock farmers at a rural level [7]. Several studies have been conducted on the estimation of body weight from various morphometric traits using different models in sheep [8], goats [9], chickens [10] and reported different traits that can be used as single predictor of body weight. However, it has been noticed that using single trait as predictor of body weight gives low precision [11].…”
Section: Introductionmentioning
confidence: 99%